Supernatural Elements in Tangon and Their Connection with Ethnic Ranau Dusun Beliefs: (Unsur-unsur Keajaiban dalam Tangon dan Perkaitannya dengan Konteks Kepercayaan Etnik Dusun di Ranau) (Malay Literature, 2019)
Storytelling (monusui) is an oral tradition handed down from generation to generation among the Dusun ethnic group in Sabah. In the past, the narration of tangon (folktales) was a form of entertainment and an informal medium of education for the Dusun ethnic. A total of 44 tangon were successfully collected during fieldworks conducted in the state of Ranau. On examining the 44 tangon, 13 were found to be stories that contain supernatural elements or elements of magic. Among these are phenomena such as "humans being resurrected", "humans giving birth to animals", "humans morphing into birds", and many more. These elements in tangon are the result of its creator's imagination and creativity. The issue here is that if these elements are not analysed and highlighted, we will not be able to comprehend the imagination, creativity, and beliefs of the previous generations. The result of the analysis by way of interpretation of these supernatural elements in tangon shows that the Ranau Dusun ethnic group had a rich imagination and a great deal of creativity in conceiving these magical elements. In addition, their beliefs, which were part of the Ranau Dusun practices in the past, were also inserted in tangon.Keywords: Magic in tangon, Ranau Dusun, creativity, supernatural elements, beliefs